Relational mobility and variety seeking : exploring multiculturalism and symbolic threat as explanatory mechanism - Chugani, Dhaneesha (2017)
In a multicultural society, could the attitudes and experiences from the environment have an impact on how a consumer makes purchasing decisions? The current study aimed to discover any potential relationships between the constructs of relational mobility, multiculturalism, symbolic threat and variety seeking behaviour, which have historically not been studied together. Relational mobility, the manipulated independent variable in question, describes an individual’s opportunity in their environment to form new relationships. Additionally, variety seeking as a dependent variable was conceptualized in 2 ways – holiday-based variety seeking and candy-based variety seeking. Multiculturalism was predicted to be related to variety seeking, with symbolic threat serving as a mediator. This prediction was partially supported. Higher multiculturalism attitudes were found to decrease perceived symbolic threat, which in turn resulted in less variety sought, specifically to the candy-based variety seeking measure. Relational mobility was predicted to have an effect on variety seeking behaviour, with multiculturalism serving as a mediator. This prediction was only partially supported as well. The sample was segregated by mood, and it was found that when participants described their experience in both positive and negative terms, multicultural experience had a marginal, indirect effect between relational mobility and holiday-based variety seeking. Relational mobility was positively related to multicultural experience, which consequently was negatively related to holiday-based variety seeking. Due to the partial support for the hypotheses, practical implications and future directions on how to utilize these findings will be discussed. Keywords – relational mobility, multiculturalism, symbolic threat, variety seeking